Mesenchymal Stem Cells in Hematopoietic Stem Cell Transplantation - Battiwalla, Minoo (2009)
Mesenchymal stromal/stem cells (MSCs) of bone marrow (BM) origin not only provide the supportive microenvironmental niche for hematopoietic stem cells (HSCs) but are also capable of differentiating into various cell types of mesenchymal origin, such as bone, fat, and cartilage. In vitro and in vivo data suggest that MSCs have low inherent immunogenicity, modulate/suppress immunological responses through interactions with immune cells, and home to damaged tissues to participate in regeneration processes through their diverse biological properties. MSCs derived from BM are being evaluated for a wide range of clinical applications including disorders as diverse as myocardial infarction or newly diagnosed diabetes mellitus type-1. However, their use in HSC transplantation, either for enhancement of hematopoietic engraftment or for treatment/prevention of graft versus host disease, is far ahead of other indications. Ease of isolation and ex vivo expansion of MSCs, combined with their intriguing immunomodulatory properties, and their impressive record of safety in a wide variety of clinical trials make these cells promising candidates for further investigation.